Stem cell markers expression evaluation in Oral Squamous Cell Carcinoma (Research, Society and Development, 2021)
Oral carcinogenesis is a highly complex process. Molecular studies demonstrate that some oral cancers progress from pre-neoplastic lesions. Cancer stem cells (CSCs), a small cellular group within the tumor, have currently received much attention by its self-renewal and tumor differentiation ability. It is considered that CSCs may be responsible for the relapse and metastasis of cancer. CSCs have been reported to express common embryonic stem cells markers such as Nestin and Nanog. The aim of the present study was to identify the presence of Nestin and Nanog markers in patients with oral squamous cell carcinoma (OSCC). Nine samples were collected from patients diagnosed with OSCC and two healthy oral mucosa were used as control. The markers expression in nine OSCC was determined by end-point PCR. The OSCC population analyzed was mostly composed of black and white males, with a mean age of 70.6 years, that reported alcohol and tobacco consumption. Nestin and Nanog stem cell markers were expressed in all OSCCs and normal samples analyzed. As these two markers have already been related to the mechanism of metastasis and relapses in cancer, its expression determination could help to understand the aggressive and invasive nature of OSCC.